Quantification of spray coverage on grape bunch parts and the incidence of Botrytis cinerea - Brink, Jan-Cor (Johannes Cornelius) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2005.